Pelatihan, Pengembangan, dan Manajemen Karir Training Effectiveness - Career Path & Talent Development - Juan Areza Fernanda; Singgih Puji Raharjo; Arfiani Yulianti Fiyul (STID Raudlatul Iman Sumenep, 2026)
The rapid advancement of technology and globalization has triggered significant disruptions in the skills required in the modern workforce, resulting in a widespread skills gap phenomenon. Amid organizational demands to continuously adapt and remain competitive, employees face psychological challenges such as anxiety, mental exhaustion, and fears of losing the relevance of their competencies. This conceptual article examines the urgency of strategically integrating training, development, and career management through a more humanistic and human-centered approach. Through a literature review and synthesis of contemporary Human Resource Management theories, this study explores key factors influencing training effectiveness, including the 70:20:10 Model, Andragogy Theory, and the Kirkpatrick-Phillips Evaluation Model, as well as the role of talent development through the 9-Box Matrix, Dual Career Paths, and Individual Development Plans (IDPs). The findings indicate that the effectiveness of human resource development can no longer be measured solely by financial Return on Investment (ROI); rather, it should be assessed by the extent to which organizations humanize their workforce through the alignment of strategic business objectives with employees' personal aspirations. Empathetic integration through Individual Development Plans (IDPs) is shown to serve as a vital bridge in developing resilient, adaptive talent with high levels of intrinsic satisfaction in a VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) environment. Kemajuan teknologi dan globalisasi yang pesat telah memicu gangguan yang signifikan dalam keterampilan yang dibutuhkan dalam tenaga kerja modern, mengakibatkan fenomena kesenjangan keterampilan yang meluas. Di tengah tuntutan organisasi untuk terus beradaptasi dan tetap kompetitif, karyawan menghadapi tantangan psikologis seperti kecemasan, kelelahan mental, dan ketakutan kehilangan relevansi kompetensi mereka. Artikel konseptual ini mengkaji urgensi mengintegrasikan pelatihan, pengembangan, dan manajemen karir secara strategis melalui pendekatan yang lebih humanistik dan berpusat pada manusia. Melalui tinjauan literatur dan sintesis teori Manajemen Sumber Daya Manusia kontemporer, penelitian ini mengeksplorasi faktor-faktor kunci yang mempengaruhi efektivitas pelatihan, termasuk Model 70:20:10, Teori Andragogi, dan Model Evaluasi Kirkpatrick-Phillips, serta peran pengembangan bakat melalui Matriks 9-Kotak, Jalur Karir Ganda, dan Rencana Pengembangan Individu (IDP). Temuan tersebut menunjukkan bahwa efektivitas pengembangan sumber daya manusia tidak lagi dapat diukur hanya dengan Return on Investment (ROI) finansial; sebaliknya, itu harus dinilai dengan sejauh mana organisasi memanusiakan tenaga kerja mereka melalui penyelarasan tujuan bisnis strategis dengan aspirasi pribadi karyawan. Integrasi empati melalui Rencana Pengembangan Individu (IDP) terbukti berfungsi sebagai jembatan vital dalam mengembangkan talenta yang tangguh, adaptif dengan tingkat kepuasan intrinsik yang tinggi dalam lingkungan VUCA (Volatility, Uncertainty, Complexity, and Ambiguity).